Memikirkan Ulang Konsep Kesalahan : Tantangan Gen MAOA terhadap Pertanggungjawaban Pidana - Zul Khaidir Kadir (Lembaga Pengembangan Kinerja Dosen, 2025)
The modern doctrine of criminal responsibility is built on the premise of free will and individual deliberative capacity. However, advances in neurogenetics, particularly findings regarding MAOA-L gene expression, have presented a structural disruption to this framework. The MAOA-L gene has been empirically associated with impaired impulse regulation and increased aggressive responses, particularly in combination with childhood trauma. This study aims to evaluate how MAOA-L gene expression influences the capacity for criminal responsibility and to analyze the tension between classical legal constructs and biological determinants within the structure of culpability. The research method employed normative research with a conceptual approach. The results indicate that the dichotomy-based mens rea doctrine fails to accommodate the degree of control capacity shaped by neurobiological structures. MAOA-L cannot be treated as a basis for forgiveness, but rather serves as an evaluative variable in assessing the spectrum of legal responsibility. In this position, criminal law maintains the principle of individual responsibility but formulates it through a new framework based on actual capacity rather than a universal voluntaristic assumption. This reformulation is necessary to avoid disproportionate attribution of blame and to allow criminal law to move toward a system that is more adaptive to biological realities without falling into determinism.